Teacher citizen: First Amendment balancing test - Sands, John, author; Davies, Timothy Gray, advisor (Colorado State University. Libraries, 2008)
This study provides insight into the life of a relatively unknown character in the continued struggle to defend freedom of speech for public employees. This struggle is portrayed in the life chronicles of Marvin Pickering, a retired public high school science teacher. Written in the life history tradition, this study provides the reader with the story before, during, and after Pickering's journey through a prominent Supreme Court decision. While much has been written about notable legal scholars, justices, and prominent attorneys involved in Supreme Court cases, relatively little has been written about the lives of "common" participants. The examination of this life story of one man's experience results in the broadening of understanding and contributes to the body of knowledge related to public employee freedom of speech matters. My interviews with this individual resulted in an in-depth portrait of his journey as it emerged. The insight may be used by leaders in the field of education or other administrative officials charged with managing public employees. The study will provide a better understanding of the impact of policies and actions that restrict public employees' rights to free speech.
Keywords: biographical life study; due process; First Amendment; free speech; Pickering, Marvin; public employers; teacher citizen; biographies; law; school administration; education history; educational administration